Diversi Dalam Penyelesaian Perkara Anak Yang Berhadapan Dengan Hukum Oleh Jaksa Penuntut Umum (Studi Kasus Di Kejaksaan Negeri Sukoharjo) - Putri, STtevani Aristra, Sudaryono,SH., M.HUM, Bambang Sukoco S.H.,M.H (2016)
The purpose of this research is to show the procedure of Diversion to child who have problem with laws accused by Prosecutor and the problematic factor in Diversion and the solution for it. The method for this research is juridical empirical law. Type of research that will be used is descriptive. From the result of research in how to do Diversion by Prosecutor based on the civil law No 11 year 2012 about Child Punishment System and Prosecutor rule PER-006/A/J.A/05/2015 about How to do Diversion in Making Charges. The conclusion of this research is there is a match between a guide to do Diversion and the application of Diversion by the Prosecutor in making charges from Sukoharjo district attorney. The problem in Diversion is the accused didn't come, lack of knowledge on Diversion and there is no room for Diversion. Solution for the problem is the coinsience of the accused, an understanding of law and make a room for diversion.